2020
DOI: 10.1364/ol.393917
|View full text |Cite
|
Sign up to set email alerts
|

Active terahertz time differentiator using piezoelectric micromachined ultrasonic transducer array

Abstract: The rapid growth of information technology is closely linked to our ability to modulate and demodulate a signal, whether in the frequency or in the time domain. Recent demonstrations of terahertz (THz) modulation involve active semiconductor metamaterial surfaces or use of a grating-based micromirror for frequency offset tuning. However, a wideband and active differentiator in the THz frequency band is yet to be demonstrated. Here, we propose a simple method to differentiate a THz pulse by inducing tiny phase … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 24 publications
0
4
0
Order By: Relevance
“…Microelectromechanical system (MEMS) technology enables micro/nanoscale mechanical manipulation, which is suitable for meta-atom construction in the THz region, bringing various applications in THz functional devices. The reconfigurable MEMS metamaterials can be further classified by their actuator mechanisms, such as piezoelectric ( Willatzen and Christensen, 2014 ; Amirkhan et al., 2020 ; Le et al., 2022 ), electrothermal ( Lee and Wu, 2005 ; Lee and Yeh, 2005 ; Lee, 2005 ; Lee, 2006 ; Lee, 2007 ; Pitchappa et al., 2017 ), and electrostatic ( Pitchappa et al., 2015a , 2015b , 2015c , 2016a , 2016c ; Shih et al., 2017 ) ( Pitchappa et al., 2021a , 2021b ), and so on ( Lee et al., 2005 ; Lee, 2005 ; Yeh et al., 2006 ). Combining with metamaterial resonator designs, the deformed structures can effectively modify the electromagnetic field distribution inside the resonators.…”
Section: Tuning Mechanisms Of Thz Reconfigurable Metamaterialsmentioning
confidence: 99%
See 1 more Smart Citation
“…Microelectromechanical system (MEMS) technology enables micro/nanoscale mechanical manipulation, which is suitable for meta-atom construction in the THz region, bringing various applications in THz functional devices. The reconfigurable MEMS metamaterials can be further classified by their actuator mechanisms, such as piezoelectric ( Willatzen and Christensen, 2014 ; Amirkhan et al., 2020 ; Le et al., 2022 ), electrothermal ( Lee and Wu, 2005 ; Lee and Yeh, 2005 ; Lee, 2005 ; Lee, 2006 ; Lee, 2007 ; Pitchappa et al., 2017 ), and electrostatic ( Pitchappa et al., 2015a , 2015b , 2015c , 2016a , 2016c ; Shih et al., 2017 ) ( Pitchappa et al., 2021a , 2021b ), and so on ( Lee et al., 2005 ; Lee, 2005 ; Yeh et al., 2006 ). Combining with metamaterial resonator designs, the deformed structures can effectively modify the electromagnetic field distribution inside the resonators.…”
Section: Tuning Mechanisms Of Thz Reconfigurable Metamaterialsmentioning
confidence: 99%
“…Microelectromechanical system (MEMS) technology enables micro/nanoscale mechanical manipulation, which is suitable for meta-atom construction in the THz region, bringing various applications in THz functional devices. The reconfigurable MEMS metamaterials can be further classified by their actuator mechanisms, such as piezoelectric (Willatzen and Christensen, 2014;Amirkhan et al, 2020;Le et al, 2022), electrothermal Lee, 2005;Lee, 2006;Lee, 2007;Pitchappa et al, 2017), and electrostatic (Pitchappa et al, 2015a(Pitchappa et al, , 2015b(Pitchappa et al, , 2015c(Pitchappa et al, , 2016a(Pitchappa et al, , 2016cShih et al, 2017)…”
Section: Microelectromechanical System Tuning Mechanismsmentioning
confidence: 99%
“…Additionally, a more recent work has showed that the phase‐modulation induced by a piezoelectric micromachined device onto a THz pulse could lead to its time differentiation. [ 38 ] We note that, in both cases, the subwavelength feature of the employed devices is the key aspect allowing for a broadband operation. Nevertheless, such solutions have been implemented in a free space configuration, which makes difficult to realize full, compact and portable THz systems.…”
Section: Introductionmentioning
confidence: 99%
“…ultrasonic transducers (MUTs), and that new applications are enabled thanks to their properties. For example, it has been shown that PMUTs can act as an active terahertz time differentiator [11][12][13], in which case the periodic displacement of the membrane is of interest to affect the terahertz signal.…”
mentioning
confidence: 99%